Aneurin Bevan's long shadow over 70 years of the British National Health Service. (May 2018) - Powell, Martin
The years approaching the 70th anniversary of the British National Health Service (NHS) have seen some re-assessment of the role of the Labour party in general, and Minister of Health, Aneurin Bevan in particular, in the creation of the NHS. It is clear that Bevan casts a long shadow over the NHS. In terms of 'history as invocation', Bevan can be invoked in different ways. Put another way, different Bevans cast a variety of shadows. This article explores: Bevan as the embodiment of the NHS; Bevan as rhetoric; Bevan as trust; and Bevan as reassurance. It concludes that Bevan has rightly cast his long shadow over the 70 years of the NHS. However, it is important to recognise the different Bevan reference points for their different reasons. However, there is one surprising omission. As a present to the NHS on its 70th birthday, perhaps it is time to rename this type as a 'Bevan' system?